The Size of Government and U.S.-European Differences in Economic Performance - Bell, Gerwin (IMF Working Papers; Working Paper ;, 2009)
An influential strand of recent research has claimed that large governments in European countries explain their weaker long-term economic performance compared to the U.S. On the other hand, despite these alleged costs, large governments have been popular with electorates. This paper seeks to shed light on this apparent inconsistency; it confirms an adverse effect of taxes on labor supply, but also finds evidence of efficiency-increasing government intervention. However, and especially in the core "Rhineland-model" European countries, actual government policies often depart from such efficient interventions, pointing to the possibility that voters prefer redistribution even at the cost of allocational efficiency.